دراسة تأثير التردد والسعة على مردود الأفران التحريضية على شكل الحوجلة - بدور جهاد (Latakia University Journal -Engineering Sciences Series, 2019)
يقاس تطور أي بلد صناعياً بمدى قدرته على صهر وتشكيل المعادن بمختلف أنواعها. استخدمت طرق عديدة لصهر تلك المعادن، كالأفران التي تعمل على الفحم الحجري والوقود وغيرها، حيث يصدر عنها مواد ملوثة لها تأثيرها السلبي على الوسط الخارجي، والكائنات الحية، لذلك تم دراسة طريقة حديثة لصهر المعادن هي الفرن التحريضي على شكل حوجلة، إعداد نموذج رياضي، وتحديد البارامترات الأفضل لعمل الفرن، المقاومة النوعية والتردد ومعرفة مدى تأثيره على البيئة. The development of any industrial country is measured by its ability of melting and forming the metal in various types. Many methods have been used to melt these metals. Such as carbon stone furnace and fuel furnaces, etc. where radiate some bad materials which have negative impact on outdoor environment and creatures. So, it is important to design and study modern method to melt the metals which is crucible shape inductive furnace. Also, it has been prepared mathematical model and defined the optimal parameters of furnace works, such as resistance and frequency and also to know its effect on the environment.